ANALISIS POLIMORFISME GEN (eNOS) DAN ESTRADIOL PADA PENDERITA ENDOMETRIOSIS - Lidya, Metri; Metti, Elvia; Muchtar, Murniati; Syahdia, Yolanda; Permata, Rani Intan (Media Penelitian dan Pengembangan Kesehatan, 2023)
Endometriosis is characterized by inflammation and is an estrogen-dependent disease that affects 6-10% of women during their reproductive years and up to 50% of women who received fertility treatment. The purpose of this study was to determine the relationship between endothelial nitric oxide synthase gene polymorphisms (eNOS) and levels of the hormone estradiol. This type of research is an analytic observational study with a comparative cross-sectional study design where the dependent and independent variables are obtained simultaneously. The research was conducted in hospitals types B and C in Padang city and the Biomedical Laboratory of FK Unand. The population is all patients in the obstetrics and gynecology department of the hospital. Samples were taken sequentially that met the inclusion and exclusion criteria for a sample of 40 people. Data analysis was univariate, and bivariate with a chi-square test. The results showed that there was an Enos gene polymorphism in endometriosis patients and most in the GG genotype casein, most endometriosis patients had high estradiol levels ( >40 pg / ml) and there was a relationship between eNOS gene polymorphism with estradiol levels in the blood serum of endometriosis patients p = 0.04. It can be concluded that there was an Enos gene polymorphism in endometriosis patients and most in the GG genotype casein. Patients with endometriosis have high estradiol levels. There was a relationship between estradiol levels and the eNOS gene in endometriosis patients.